Schooling and self-control - Deborah A. Cobb-Clark; Sarah C. Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
While there is an established positive relationship between self-control and education, the direction of causality remains a matter of debate. We make a contribution to resolving this issue by exploiting a series of Australian and German educational reforms that increased minimum education requirements as a source of exogenous variation in education levels. Instrumental variables estimates suggest that, for people affected by the reforms, an additional year of schooling has no effect on self-control.
Keywords: D90; I26; C26; 330; self-control; quasi-experiments; compulsory schooling reforms; Brief Self-Control Scale